Primary kidney malignant epithelioid angiomyolipoma: Two cases report and review of literature. Issue 32 (August 2018) - Zhan, Rui; Li, Yan-Qing; Chen, Chun-Yan; Hu, Han-Yu; Zhang, Chun
Abstract: Rationale: Epithelioid angiomyolipoma (EAML) is a subtype of angiomyolipoma with malignant potential. A diagnosis of malignant EAML of the kidney is based on extrarenal metastasis, and predicting early transformation is difficult. To propose criteria for indicators of malignant transformation, herein we report 2 cases and review 17 cases reported in the literature (2000–2017). Patient concerns: Tumor of the kidney was determined in 2 patients, and tissues after nephrectomy were pathologically, histologically, and immunochemically examined. Diagnosis: Malignant EAML. Intervention: The 2 present patients were treated with nephrectomy only. Outcomes: Case 1 involved a 48-year-old woman with a 7.5-cm solid mass in the right kidney who underwent nephrectomy. CT detected a mass in the liver after 13 months, which was speculated to be metastasis from the kidney lesion. Case 2 involved a 62-year-old man with a 7-cm cystic solid mass in the left kidney who accepted nephrectomy and at 10 months post-surgery lived with no disease. Both cases presented a large tumor, atypical epithelioid cells, mitotic figures, and necrosis; tested positive for melanocytic markers (HMB45, MelanA). Lessons: The literature review of malignant EAML led to the identification of 8 malignant features: size ≥5 cm; metastasis; infiltration; necrosis; ≥50% atypical epithelioid cells; cytologic atypia; atypical mitosis; and vessel invasion. The co-existence of at least 5 of these is proposed to indicate malignant EAML. Features of our 2 new cases of primary malignant EAML of the kidney matched these criteria. Our proposal of criteria for predicting malignant feature, based on 2 new cases and 17 cases in the literature, should aid understanding and avoid misdiagnosis. Nephrectomy is currently the common treatment strategy for malignant EAML, but more effective treatment strategies are needed to provide a better prognosis for patients.